2007
DOI: 10.1021/es070789e
|View full text |Cite
|
Sign up to set email alerts
|

Deposition versus Photochemical Removal of PBDEs from Lake Superior Air

Abstract: Analysis of a sediment core collected from Siskiwit Lake, located on a remote island in Lake Superior, provides evidence that polybrominated diphenyl ethers (PBDEs) are removed effectively from the atmosphere via deposition processes during long-range transport. A mass balance model based on photochemical rate constants and data from atmospheric samples was created to understand the relative importance of various photochemical and deposition processes in removing PBDEs from the atmosphere. Photolysis rate cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 36 publications
6
100
2
Order By: Relevance
“…The authors suspected that these decomposition products were either formed during LRAT by photodegradation or by biodegradation once DP entered into the ocean (Möller et al, 2010). Although photodegradation of DP was observed in the simulation experiment by Sverko et al (2008), Raff and Hites (2007) indicated that atmospheric particle bound semivolatile organic compounds (SOCs) might not be photodegradated due to the shielding effect of carbonaceous aerosols on sorbed SOC molecules. However, thermal degradation of DP may occur during e-waste burning processes since the recommended operating temperature of DP is 285°C, and decomposition may occur at 350°C (OxyChem, 2007).…”
Section: Dp Dechlorinated Analogsmentioning
confidence: 99%
“…The authors suspected that these decomposition products were either formed during LRAT by photodegradation or by biodegradation once DP entered into the ocean (Möller et al, 2010). Although photodegradation of DP was observed in the simulation experiment by Sverko et al (2008), Raff and Hites (2007) indicated that atmospheric particle bound semivolatile organic compounds (SOCs) might not be photodegradated due to the shielding effect of carbonaceous aerosols on sorbed SOC molecules. However, thermal degradation of DP may occur during e-waste burning processes since the recommended operating temperature of DP is 285°C, and decomposition may occur at 350°C (OxyChem, 2007).…”
Section: Dp Dechlorinated Analogsmentioning
confidence: 99%
“…In the Canada Basin, the concentration of BDE-183 was at the same level with that of BDE-153 while, on the contrary, no BDE-183 was detected in the Bering Sea or the Chukchi Sea. This may indicate a local source of PBDEs from North America (de Wit et al, 2010;Raff and Hites, 2007). Furthermore, the ability of the particlebound congeners to increase with a decrease in temperature together with the relatively low concentrations of PBDEs, suggest that atmospheric deposition was also a significant input pathway Raff and Hites, 2007;Rayne et al, 2003;Su et al, 2007).…”
Section: Regionmentioning
confidence: 99%
“…This may indicate a local source of PBDEs from North America (de Wit et al, 2010;Raff and Hites, 2007). Furthermore, the ability of the particlebound congeners to increase with a decrease in temperature together with the relatively low concentrations of PBDEs, suggest that atmospheric deposition was also a significant input pathway Raff and Hites, 2007;Rayne et al, 2003;Su et al, 2007). However, normality tests show that the skewness was 0.410-1.455 for P PBDEs and 1.057-2.506 for BDE-209, which further indicated that the distribution of PBDEs was not only dominated by atmospheric deposition (Su et al, 2007) but also by some local source from the coastal area.…”
Section: Regionmentioning
confidence: 99%
“…), which was different from BDE-209. This is likely because that these lighter congeners are more mobile in the atmosphere while BDE-209 could be removed from the atmosphere via particle deposition during transport (Raff and Hites, 2007). BDE-47 has similar or higher concentrations at rural sites than urban sites, which might be due to the contributions of both atmospheric transport and local sources.…”
Section: Difference In Congener Profile Among the Sitesmentioning
confidence: 99%